Juniperus L. for Restoration of Degraded Forest Lands in Turkey - Yücedağ, Cengiz (Array, 2021)
Degraded forests are among of the most important environmental and commercial problems around the world. Turkey has 22.74 million hectares of forest area, out of which 9.656 million ha (42%) are unproductive. To transform these unproductive forests into productive ones, forest restoration including rehabilitation is one of the best actions. In this sense, juniper species play an important role for degraded lands because they are drought-tolerant and withstand aridity and poor soils better than most timber species grown in Turkey. Therefore, this review presents the ecological considerations for the restoration of degraded forest lands in Turkey under the conditions of climate change. Within this framework, it focuses on the production of planting stock of juniper species, the significance of site-species matching, and post-planting site maintenance for successful rehabilitation.